Inventory redistribution based on ABC classification to improve material flow in a food production company in Sinaloa, Mexico - Flores Gutiérrez, Xóchitl Patricia (2023)
The goal of this research is to carry out an inventory redistribution following the ABC classification of merchandise, as well as gauge improvement in indicators of inventory rotation and duration in a food production company in Sinaloa, Mexico. The methodology employed comprised 4 stages: a diagnosis of the current situation, generation of inventory redistribution proposals based on ABC classification, implementation and evaluation of results. Inventory rotation and duration performance indicators were measured prior and following implementation, achieving favorable results across 5 products with butter as the standout, whose weekly rotation was increased by 32,92 units while its warehouse time was cut by two days. The information was collected by observing and counting physical inventory units paired with verifying the inventory in the system. The study concluded that inventory management is a key activity for any organization, food companies in particular, since the products are perishable and prone to generating loss where it is not properly managed or rotated.